Leadership and Entrepreneurial Choices: Understanding the Motivational Dynamics of Women Entrepreneurs in Iran - Marcus Goncalves; Sadaf Sartipi; Ghazale Asadi Damavandi (Merits)
This study explores the motivations and constraints of Iranian women entrepreneurs within a restrictive socioeconomic and cultural landscape. It adopts a qualitative approach and utilizes semi-structured interviews to investigate the complex interplay between financial limitations, gender biases, and regulatory challenges entrepreneurs face. These findings underscore the importance of resilience, adaptability, and creativity for entrepreneurial success. Women entrepreneurs in Iran adopt incremental growth strategies, utilize digital platforms for market access, and cultivate informal networks to manage risks and scale their ventures. They also creatively integrate family responsibilities into their business models, highlighting the cultural shaping of their entrepreneurial activities. The concept of regulatory adaptation was introduced to illustrate how entrepreneurs restructure their operations to comply with stringent government regulations while sustaining growth. The emotional burden of navigating these hurdles is also evident, emphasizing the need for support mechanisms that address mental health and well-being. Policy implications are discussed, and enhancements in financial access, gender equality, digital entrepreneurship, and mental health support for women entrepreneurs are recommended. This study contributes to the entrepreneurship theory by understanding how sociocultural contexts influence women’s entrepreneurial activities and resilience strategies.